Logistics Management Contributions of the Section Logistics of the German Academic Association for Business Research, 2015, Braunschweig, Germany - Mattfeld, Dirk; Spengler, Thomas; Brinkmann, Jan; Grunewald, Martin (Lecture Notes in Logistics, 2016)
This contributed volume contains the selected and thoroughly reviewed research papers presented at the conference on logistics management LM2015 in Braunschweig, Germany. The conference of the special interest group in logistics of the German Academic Association for Business Research (VHB) was held in conjunction with the special interest group on production of the VHB. Thus, the papers reflect the current state-of-the-art in logistics and supply chain management while focusing especially on aspects of production logistics, i.e., facility layout, inventory management, line configuration, or flexible production.